THE ROLE OF PERCEIVED SECURITY AS A MODERATOR IN SMES CONSUMERS’ INTENTION TO ADOPT QRIS AS A PAYMENT METHOD - Garnita, Marlin Faishal; Oktavian, Panji; Ananda, Artha Sejati (LPPM Universitas Jambi, 2026)
The increasing popularity of QR code mobile payment systems highlights their convenience and efficiency in facilitating contactless transactions. These systems enable consumers to make quick purchases and complete payments through their mobile devices. This study aims to examine the factors influencing user acceptance of the Quick Response Code Indonesian Standard (QRIS) payment system and to uncover the causal relationships between these factors. To achieve this, the study extends the Technology Acceptance Model (TAM) by incorporating perceived security as a moderating variable. Data for this research was collected from 198 QRIS users in Indonesia via an online survey. The findings reveal that perceived security plays a significant moderating role by strengthening the relationships between perceived ease of use, perceived usefulness, and intention to adopt. These findings contribute to the refinement of TAM in digital payment contexts and provide practical insights for policymakers and fintech providers to strengthen security communication and system reliability in order to accelerate QR code payment method.